Pengaruh Pemeliharaan Dan Pengendalian Kualitas Terhadap Tingkat Produk Gagal Di PT.Granesia (Studi Kasus Pada Divisi Produksi Buku Percetakan) - Dudi Haryadi (Lembaga Penelitian Universitas Langlangbuana, 2019)
The product fails to be a product that cannot be categorized as a final product and is economically or technically irreversible so that it should be discarded or sold below the sale price of the final product, due to the factors affecting the failure Products are the maintenance and quality control factors to minimize product failure rates. Through this research the author intends to further analyze the maintenance and control of quality that affect the failure of failed products in PT. Granesia. The effectiveness of resources is crucial to face the various challenges of the company both internally and externally to maintain the quality of the product. Through increased ability employees are expected to obtain a competent workforce that will reduce the failure rate of products produced by the company. Therefore, the descriptive and Vericular methods become the author's choice with the subject of production division employees. The instrument is used through the validity and reliability test first. Data collection is carried out using a questionnaire distributed with 70 questionnaires. The statistical method uses the analysis path. The results of the descriptive research on the production division of PT. Granesia showed that maintenance is already good, the quality control assessed is good and the product level fail to be assessed low. The results of the verificative studies indicate that there is an influence on the maintenance and quality control of the production division of PT. Granesia. Based on the results The study showed that PT. Granesia maintenance significantly affects the product's level of failure. Quality control has significant effect on the failing product level. Quality maintenance and control are simultaneously influential.